Safety NATO Policy in Developing Polish Security Sector - Czerski, Robert; Kustra, Marek; Goniewicz, Krzysztof (Journal of Education, Health and Sport, 2019)
Participation of countries in international alliances stems from a desire to increase the level of national security through the support of its own defense capabilities guarantees the assistance provided by the allies. The North Atlantic Treaty was based on the concept of collective defense of the member countries against various types of threats. Polish membership in NATO recognizes the importance of the Alliance as an entity acting on behalf of the global and regional security. The aim of the study was to present and analyze the impact of Polish membership in NATO at the level of security of the state. Deliberations on this matter are useful for policy and military sector, they enable to describe the facts and indicate the arguments in favor of participation in the alliance.